Treatment Of Young Leachate Using Electrocoagulation Process - Mohd Yusoff, Nur Hayati (Universiti Sains Malaysia, 2018)
Landfilling is one of the most popular methods of municipal solid waste disposal due to its simplicity in terms of disposal and low cost. One of the main problems with the solid waste landfill sites is leachate depending on large amount of organic matter, ammonia, nitrogen and heavy metals. Young leachate tends to be acidic due to presence of volatile fatty acid with pH normally in the range of 6-7 or lower. Leachate contains a variety of organic and inorganic contaminants and is classified as problematic and extremely dangerous pollutants to ecosystem as it can percolate through permeable soil and can pollute groundwater. In this study, electrocoagulation process was used as an alternative to treat leachate. This method is characterized by simple equipment and easy operation. The overall objectives of this study was to determine the optimum treatment condition that influence the efficiency of electrocoagulation method to treat leachate wastewater. There are three control parameters that need to be considered during this test such as voltages, treatment time and the present of sodium chloride as electrolyte. Carbons were used as electrode for both cathode and anode with or without sodium chloride. The ranges of voltages applied were 3V, 6V, and 9V and the ranges of treatment time were 10 minutes, 20 minutes, 30 minutes and 40 minutes. The research work involve the analysed of effects on colour, turbidity, Chemical Oxygen Demand (COD), total suspended solids (TSS). The optimum removal of color, turbidity, COD and total suspended solids were 6V with 10 minutes treatment time, 3V with 30 minutes treatment time, 9V with 40 minutes treatment time and 6V with 30 minutes treatment time respectively. Therefore, the percentage efficiency of pollutant removal on color, turbidity, COD and total suspended solids were 97.34%, 42.54%, 54.98% and 86.76% respectively. Therefore, electrocoagulation is proven in treated young leachate effectively.